The Role of Environmental Impact Assessment in Sustainable Development: A Review of Legal Perspectives - Kemmala Dewi (Law Studies and Justice Journal (LAJU), 2024)
Environmental Impact Assessment (EIA) is a vital process in sustainable development, providing a systematic approach to identifying, predicting and evaluating the environmental impacts of proposed actions and projects. This research aims to explore the role of EIA as a legal tool in facilitating cross-border collaboration to support global sustainable development. Using the PRISMA method for systematic literature review, this research finds that consistent implementation and regulation of EIA can increase cross-border cooperation in environmental management. The research results show that EIA not only supports better decision making but also strengthens the legal framework for achieving sustainable development goals.